Single-incision open versus laparoscopic gastrostomy in infants: A comparative study - Osama A Bawazir; Ahmed Hasan Alamoudi (Wolters Kluwer Medknow Publications, 2023)
Background: Gastrostomy tube can be inserted through a single incision without laparoscopic or endoscopic guidance. The superiority of this approach over the laparoscopic technique is still debated. Therefore, we aimed to compare single-incision open and laparoscopic gastrostomy in infants. Materials and Methods: We retrospectively reviewed paediatric patients aged 12 months or less who required enteral feeding between 2006 and 2019. Patients were grouped according to the technique into two groups. Group 1 (n = 42) included patients who had a single incision open gastrostomy, and Group 2 (n = 45) included patients who underwent laparoscopic gastrostomy. Results: The median age was 2 months (Q1-Q3: 1-4 months) in Group 1 and 5 months (3-6 months) in Group 2 (P < 0.001). Male presented 52.38% in Group 1 and 37.78% in Group 2 (P = 0.17). There were no differences in cardiac and neurological comorbidities between the groups. Operative time was significantly shorter in Group 1 (23 [20-25] vs. 40 [35-45] min; P < 0.001). There were no differences in the post-operative leak around the tube (P > 0.99), granulation tissue formation (P = 0.36), wound dehiscence (P = 0.61), surgical site infection (P > 0.99) and pneumonia (P = 0.10) between the groups. Conclusion: Single-incision open and laparoscopic gastrostomy could be effective and safe techniques in infants. The minimal anaesthesia without gas insufflation and short time for the open gastrostomy make it not inferior to laparoscopic gastrostomy and should be considered in small infants.